Menelusuri Jati Diri dalam Cermin Digital: Studi Kualitatif Terhadap Pengalaman dan Tantangan Pembentukan Identitas Dewasa Awal - Albarkah, Mutiara Shofia; Naila, Ainaya Zalfa; Rahmadina, Meisya; Wibawa, Rikhamelia Adi; Putri, Raissa Dwifandra (Universitas Negeri Malang, 2025)
This study aims to explore the subjective experiences and challenges of identity formation among emerging adults within the dominance of digital culture. In an era marked by an overwhelming stream of information and the portrayal of seemingly flawless lives on social media, many emerging adults find themselves disoriented in their search for self-identity. The disconnect between their genuine selves and the pressure to maintain a polished digital persona often leads to existential struggles. Using a qualitative approach and thematic analysis, this research involved in-depth interviews with eight participants aged 19 to 22. The findings reveal real-life accounts of identity uncertainty, the feeling of falling behind, and the social pressures embedded in today's digital environment. Upward social comparisons and the Fear of Missing Out (FoMO) surfaced as central contributors to feelings of inadequacy and lack of direction. Nevertheless, participants demonstrated resilience through various coping approaches, ranging from personal reflection to the reaffirmation of core values. These findings highlight the importance of emotional literacy and the courage to stay authentic in a world that constantly demands perfection. AbstrakPenelitian ini bertujuan untuk mengeksplorasi pengalaman subjektif dan tantangan pembentukan identitas pada individu dewasa awal di tengah dominasi budaya digital. Di tengah gelombang informasi yang terus mengalir dan gambaran hidup yang tampak ideal di media sosial, banyak individu pada fase dewasa awal merasa kehilangan arah dalam pencarian identitas diri. Ketidaksesuaian antara jati diri yang otentik dan tuntutan untuk menampilkan citra diri secara digital kerap memicu krisis eksistensial. Dengan menggunakan pendekatan kualitatif dan teknik analisis tematik, penelitian ini melibatkan wawancara mendalam dengan delapan partisipan berusia 19–22 tahun. Hasil penelitian menggambarkan pengalaman nyata terkait kebingungan identitas, perasaan tertinggal, serta tekanan sosial dalam budaya digital. Perbandingan sosial ke atas dan fenomena Fear of Missing Out (FoMO) muncul sebagai pemicu dominan dari rasa tidak cukup dan disorientasi arah hidup. Meski demikian, partisipan menunjukkan ketahanan melalui strategi koping seperti refleksi pribadi dan penguatan nilai-nilai diri. Temuan ini menegaskan pentingnya literasi emosional dan keberanian untuk tetap autentik di tengah tuntutan kesempurnaan digital.